Early cerebral small vessel disease and brain volume, cognition, and gait - Smith, Eric E.; O'Donnell, Martin; Dagenais, Gilles; Lear, Scott A.; Wielgosz, Andreas; Sharma, Mukul; Poirier, Paul; Stotts, Grant; Black, Sandra E.; Strother, Stephen; Noseworthy, Michael D.; Benavente, Oscar; et al. (Annals of neurology, 2015)
Objective Decline in cognitive function begins by the 40s, and may be related to future dementia risk. We used data from a community‐representative study to determine whether there are age‐related differences in simple cognitive and gait tests by the 40s, and whether these differences were associated with covert cerebrovascular disease on magnetic resonance imaging (MRI). Methods Between 2010 and 2012, 803 participants aged 40 to 75 years in the Prospective Urban Rural Epidemiological (PURE) study, recruited from prespecified postal code regions centered on 4 Canadian cities, underwent brain MRI and simple tests of cognition and gait as part of a substudy (PURE‐MIND). Results Mean age was 58 ± 8 years. Linear decreases in performance on the Montreal Cognitive Assessment, Digit Symbol Substitution Test (DSST), and Timed Up and Go test of gait were seen with each age decade from the 40s to the 70s. Silent brain infarcts were observed in 3% of 40‐ to 49‐year‐olds, with increasing prevalence up to 18.9% in 70‐year‐olds. Silent brain infarcts were associated with slower timed gait and lower volume of supratentorial white matter. Higher volume of supratentorial MRI white matter hyperintensity was associated with slower timed gait and worse performance on DSST, and lower volumes of the supratentorial cortex and white matter, and cerebellum. Interpretation Covert cerebrovascular disease and its consequences on cognitive and gait performance and brain atrophy are manifest in some clinically asymptomatic persons as early as the 5th decade of life. Ann Neurol 2015;77:251–261